Absolute Configuration of Alkaloids from Uncaria longiflora through Experimental and Computational Approaches - Salim, Fatimah; Yunus, Yusri Mohd; Anouar, El Hassane; Awang, Khalijah; Langat, Moses; Cordell, Geoffrey A.; Ahmad, Rohaya (American Chemical Society, 2019)
The structure elucidation of three new alkaloids named isoformosaninol (1), formosaninol (2), and longiflorine (3), isolated from the leaves of Uncaria longiflora var. pteropoda (Miq.) Ridsdale, along with their biosynthetic pathways are discussed. Their absolute structures were determined through a combination of physical data interpretation and quantum chemical calculations using the time-dependent density functional theory (TDDFT) method. Copyright © 2019 American Chemical Society and American Society of Pharmacognosy.